2020
DOI: 10.3389/fmicb.2020.00223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Staphylococcus aureus Plasmids Associated With Strains Isolated From Various Retail Meats

Abstract: Staphylococcus aureus is considered one of the most important foodborne bacterial pathogens causing food poisoning and related illnesses. S. aureus strains harbor plasmids encoding genes for virulence and antimicrobial resistance, but few studies have investigated S. aureus plasmids, especially megaplasmids, in isolates from retail meats. Furthermore, knowledge about the distribution of genes encoding replication (rep) initiation proteins in food isolates is lacking. In this study, the prevalence of plasmids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
(69 reference statements)
5
16
0
Order By: Relevance
“…Therefore, studies involving a larger number of isolates could provide a better picture of the clonality along the farm-to-fork continuum. A similar trend was observed in a study by Neyaz et al on the characterisation of S. aureus from various meat products where a high prevalence of tetracycline resistance was reported in two different clones [ 65 ]. A 2019 study in Italy using other typing methods, including WGS, reported 94.1% of human MRSA isolates belonging to the same epidemiological group as swine MRSA isolates [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, studies involving a larger number of isolates could provide a better picture of the clonality along the farm-to-fork continuum. A similar trend was observed in a study by Neyaz et al on the characterisation of S. aureus from various meat products where a high prevalence of tetracycline resistance was reported in two different clones [ 65 ]. A 2019 study in Italy using other typing methods, including WGS, reported 94.1% of human MRSA isolates belonging to the same epidemiological group as swine MRSA isolates [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…PVL is also considered a genetic marker for CA-MRSA due to its prominence in this epidemiological class [ 64 ]. A substantial number of isolates carried the PVL gene, corroborating a study conducted on S. aureus isolated from backyard-raised pigs and pig workers in Nigeria, with 27% of isolates harbouring PVL [ 65 ]. However, although PVL has been associated with necrotising pneumonia and joint infection in humans, its role in pigs is not thoroughly investigated; hence, the current findings should be interpreted with caution [ 66 ], as its presence does not necessarily imply diseased animals.…”
Section: Discussionsupporting
confidence: 66%
“…About 45% of the worldwide food poisoning are caused by bacteria of the genus Staphylococcus. Contamination occurs mainly during food production and storage periods, as it is during this period that temperatures are proper for the proliferation of this microorganism (Cunha et al, 2002;Neyaz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we examined temporally ZIKV-crosslinked proteins against protein components involved in major endocytic mechanisms for ZIKV internalization. Prior studies showed ZIKV infection could be prevented by lysosomotropic agents which neutralize the normally acidic pH of endosomal compartments and was also blocked by chlorpromazine 34 , 35 , indicating the requirement of clathrin-mediated endocytosis and low pH for ZIKV infection. In our study, ITGB1, HSPA8, RAB5C, RACK1, and RAB11A were crosslinked, suggesting the clathrin-mediated pathway employed by the virus to infect Vero cells.…”
Section: Resultsmentioning
confidence: 99%